Twin Peaks : fire walk with me [videorecording (Blu-Ray)] - Lynch, David, 1946-2025; Lynch, David, 1946-2025; Lee, Sheryl; Wise, Ray, 1947-; Amick, Mädchen (Criterion collection, 2017)
Follows the events of the week leading up to the death of Laura Palmer in the small town of Twin Peaks.